2022
DOI: 10.3390/bacteria1020009
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance of Neisseria gonorrhoeae in Sub-Saharan Populations

Abstract: Neisseria gonorrhoeae has become a significant global public health problem due to growing infection rates and antibiotic resistance development. In 2012, N. gonorrhoeae positive samples isolated from Southeast Asia were reported to be the first strains showing resistance to all first-line antibiotics. To date, N. gonorrhoeae’s antimicrobial resistance has since been identified against a wide range of antimicrobial drugs globally. Hence, the World Health Organization (WHO) listed N. gonorrhoeae’s drug resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…Multidrug-resistant organisms are becoming more prevalent and affecting the treatment of an expanding range of infectious illnesses [ 34 ]. As a consequence, there is an urgent need for the discovery of novel and efficient antimicrobials to combat pathogens now resistant to antibiotics [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multidrug-resistant organisms are becoming more prevalent and affecting the treatment of an expanding range of infectious illnesses [ 34 ]. As a consequence, there is an urgent need for the discovery of novel and efficient antimicrobials to combat pathogens now resistant to antibiotics [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] The emergence of multidrug-resistant bacteria necessitates the development of innovative antimicrobial agents that can combat these highly resilient pathogens. [8][9][10] Globally, the primary pharmacological agents employed for the management of gonococcal infection are third-generation cephalosporins (ceftriaxone and cefixime). [11] These agents are administered either as monotherapy or in combination with macrolides (azithromycin).…”
Section: Introductionmentioning
confidence: 99%
“…Azithromycin (AZM), a potent oral antibiotic, was approved by medical insurance for its efficacy against chlamydia infections, and due to numerous reports that suggest its commendable activity against Neisseria gonorrhoeae (N. gonorrhoeae) infection, azithromycin was then approved for N. gonorrhoeae treatment. [1,2] However, over the last few years, according to other sources, it has been observed that the susceptibility of N. gonorrhoeae infections to AZM has decreased, and strains that are resistant to AZM have surfaced. [3,4] The swift emergence of acquired antimicrobial-resistant strains of N. gonorrhoeae has significantly impeded the capacity to manage gonorrhoeae infections.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) predicted that 87 million new Neisseria gonorrhoeae ( N. gonorrhoeae ) infections occurred in people aged 15 to 49 in 2016 [ 1 ]. Sub-Saharan Africa was found to have the highest prevalence of N. gonorrhoeae [ 2 ]. Due to the development of resistance to every antimicrobial medication proposed for treatment since the introduction of sulphonamides in the 1930s, N. gonorrhoeae is a significant public health problem worldwide and is included on the WHO global priority list of antibiotic-resistant bacteria [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrate that MSM in South Africa and other African nations have a high burden of N. gonorrhoeae infections; the first two instances of cefixime-resistant N. gonorrhoeae infections in Africa were documented in the MSM community [ 9 , 14 ]. Understanding the antibiotic resistance profile of gonococcal populations in core transmission groups and those under sentinel monitoring is therefore critical for influencing clinical treatment recommendations and policy planning [ 2 , 15 ]. Surveillance is critically crucial for detecting and tracking gonococcal resistance.…”
Section: Introductionmentioning
confidence: 99%